Caja de Herramientas PDIA - Un enfoque “hazlo tú mismo” para resolver problemas complejos - Samji, Salimah; Andrews, Matt; Pritchett, Lant; Woolcock, MIchael (Center for International Development at Harvard University, 2018)
(Spanish version of he PDIA toolkit) The PDIAtoolkit is designed to gu ide you through the process of solving complex problems which requires working in teams. We call it a Do-it-Yourself (DIY) kit, where the ‘y ou’ is a committed team of 4-6 people mobilized to work together to so lve a complex problem that cannot be solved by one person.